Activity of sesame leaf extracts against the symbiotic fungus of Atta sexdens L. - Ribeiro, Stelamaris B. [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Victor, Sandra R. [UNESP]; Bueno, Odair C. [UNESP]; Hebling, Maria José Aparecida [UNESP]; Bacci Junior, Mauricio [UNESP]; Silva, Osvaldo A. [UNESP]; Fernandes, João B.; Vieira, Paulo C.; Silva, Maria F. G. F. (Sociedade Entomológica do Brasil, 1998)
O fungo simbionte Leucoagaricus gongylophorus (Möller) Singer, sin. de Rozites gongylophora Möller, cultivado pela formiga cortadeira Atta sexdens L. teve seu desenvolvimento fortemente inibido por frações obtidas das folhas de gergelim, Sesamum indicum L. (Pedaliaceae). Total inibição foi observada na concentração de 2,5 mg/ml, sendo verificada inibição de 50% com algumas frações na concentração de 1,25 mg/ml. A análise cromatográfica do extrato hexânico revelou a ocorrência de uma mistura de ácidos graxos, onde os componentes majoritários foram os ácidos tetradecanóico, hexadecanóico, octadecanóico, icosanóico, docosanóico e 9,12,15 octadecatrienóico. A separação desses compostos durante as várias etapas do fracionamento resultou em perda ou diminuição da atividade inibitória sobre o fungo, indicando que a inibição observada pode ser consequência da ação conjunta de alguns dos compostos presentes nas folhas e não de uma única substância.

The symbiotic fungus Leucoagaricus gongylophorus (Möller) Singer (syn. Rozites gongylophora Möller) cultivated by the leaf-cutting ant Atta sexdens L. had its development strongly inhibited by crude extracts obtained from leaves of sesame, Sesamum indicum L. (Pedaliaceae). With most of the fractions from these extracts total inhibition was observed at 2.5 mg/ml, whereas inhibition of 50% was observed with some fractions at 1.25 mg/ml. Chromatographic analysis of the hexane extract showed that it was composed by a mixture of fatty acids, of which tetradecanoic, hexadecanoic, octadecanoic, icosanoic, docosanoic and 9,12,15 octadecatrienoic acids were the major components. The separation of these compounds during the different steps of purification resulted in no or lower inhibitory effect for most of these fractions, indicating that the inhibitory activity observed could be due to the joint action of these compounds present in the leaf tissue, rather than to the action of a single substance.
Atividade de inibição de extratos de folha de gergelim no fungo Simbiótico de Atta sexdens L
Keywords: Insecta; Hymenoptera; gergelim; fungo simbionte; formigas cortadeiras; Insecta; Hymenoptera; sesame; mutualistic fungus; leaf-cutting ants